2016
DOI: 10.1002/hlca.201600028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diverse Oxa‐Carbocycle‐Annulated Flavones Using the Combined Claisen Rearrangement and Ring‐Closing Metathesis

Abstract: A simple and efficient route for the synthesis of oxepine‐, oxocine‐, oxepinone‐, and dioxocine‐angularly annulated flavone skeletons has been developed. The combined Claisen rearrangement and the ring‐closing metathesis are used as key steps for the construction of C7/C8–C6–C6 tricyclic core structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Gogula and Yerrabelly in 2016 synthesized a library of potentially bioactive oxepinoflavones via Claisen rearrangement and the ring‐closing metathesis using Grubbs' catalysts (Schemes 56–58). [ 12 ]…”
Section: Ruthenium‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gogula and Yerrabelly in 2016 synthesized a library of potentially bioactive oxepinoflavones via Claisen rearrangement and the ring‐closing metathesis using Grubbs' catalysts (Schemes 56–58). [ 12 ]…”
Section: Ruthenium‐catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
“…Gogula and Yerrabelly in 2016 synthesized a library of potentially bioactive oxepinoflavones via Claisen rearrangement and the ring-closing metathesis using Grubbs' catalysts (Schemes 56-58). [12] da Rocha et al in 2014 reported the synthesis of the oxepin-1,4-naphthoquinones 305 through the C-and Oalkylation of lawsone 302 with allyl bromide 179 followed by ring-closing metathesis using Grubbs' catalyst (Scheme 59). [96] Several strategies have been reported for the synthesis of these type compounds, but there are various disadvantages such as low reaction yields and production of byproducts.…”
Section: Ruthenium-catalyzed Synthesis Of Oxepine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation